NATURE OF HOECHST 33258 FLUORESCENCE ON THE NONTRYPSINIZED AND TRYPSINIZED SALIVARY GLAND CHROMOSOMES OF DROSOPHILA HYDEI - CHAKRABARTI, C.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
Nature of Hoechst 33258 fluorescence have been studied in salivary gland chromosomes of Drosophila before and after trypsinization of the chromosomes. Before trypsin treatment the intensity of Hoechst 33258 fluorescence was very bright at the chromocentre and dark band are as of polytene chromosomes but after trypsin digestion, the Hoechst fluorescence gradually decreased with the increased concentration of the trypsin solution. Gradual dull fluorescence due to increased concentration of trypsin indicates that Hoechst 33258 has a positive relation with the chromocentre and dark bands, which are the known heterochromatic regions of the polytene organization.